STAFF SCHEDULE ANALYSIS OF PHARMACY SERVICES USING SIMULATION CASE STUDY: BPJS MEDIKA ANTAPANI - Afrianda, Arif; Basri, Mursyid Hasan (Journal of Business and Management, 2017)
Abstract. BPJS (Badan Penyelenggara Jaminan Sosial) is a public health insurance agency in Indonesia. BPJS covers the services of doctors, pharmacists and others. With only a small monthly fee, people can get free health service and get free medication as well. Because of the many advantages provided byÂ  BPJS, the number of BPJS users in Indonesia increased dramatically, in 2016 there are 163,327,183 people who become BPJS users. To compensate for this increase, healthcare providers need to improve their services for the patients. One of them is a pharmacy installation. In Bandung, there are only three pharmacies of BPJS that serve the taking of chronic drugs or drugs needed in the long term that called BPJS PPK-2. One of them is BPJS Medika Antapani Pharmacy which is committed to provide the best service. According to the research, there is a close relationship between customer satisfaction with how long waiting time in pharmacy service. The cause of waiting time is staff schedule and staff allocation applied to pharmacy installation that is going well or not. This research will discuss the staff scheduling analysis at BPJS Medika Antapani Pharmacy by using simulation. For the first stage, analyzed how the business process at BPJS Medika Antapani Pharmacy. Then measure how long process time on each activity calculated using Time Study. The process time will be checked with the control chart using Minitab application and tested the data is in control or not. And finally, create a model that fits the reality conditions to run the simulation using iGrafx application. From this simulation, the staff scheduling analysis and staff allocation to cycle time, waiting time, and resource utilization are obtained. And solve the problem how the staff and allocation schedule that can minimize the cycle time and waiting time using simulation.Â Keywords: BPJS, Pharmacy Service, Pharmacy, Staff Scheduling, Waiting Time, Process Time, Time Study, Simulation, iGrafx.